A transcriptomic landscape analysis of human necrotizing enterocolitis: Important roles of immune infiltration - Zhuojun Xie; Quan Kang; Yulu Shi; Junbao Du; Hao Jiang (Pediatric Discovery)
Abstract Necrotizing enterocolitis (NEC) is one of the most common and destructive diseases in neonates and an unpredictable surgical emergency. However, the molecular pathological mechanism of NEC is still not well understood. This study was designed to provide a molecular basis for the pathogenesis of human NEC through bioinformatics analysis and immune infiltration. For RNA‐Seq, DEseq2 algorithm was used to identify differentially expressed genes (DEGs) and to perform functional enrichment analysis. Immune infiltration was analyzed by CIBERSORT algorithm. A total of 34,712 genes were detected and 7463 DEGs were identified in this study. Gene Ontology analysis revealed that DEGs were mainly involved in CCR1 chemokine receptor binding, transporter activity, growth factor binding, etc. KEGG pathway analysis showed that the DEGs were significantly enriched in the toll‐like receptor signaling pathway, Th17 cell differentiation, and cytokine–cytokine receptor interaction. The immune infiltration profiles varied significantly between NEC, NEC self‐control, and normal intestinal tissues. Finally, the expression levels of 21 DEGs were verified by reverse transcription quantitative real‐time PCR. Our findings may provide new insights into the development of NEC.